2019
DOI: 10.4102/jsava.v90i0.1671
|View full text |Cite
|
Sign up to set email alerts
|

Canine parvovirus detected from a serval (Leptailurus serval) in South Africa

Abstract: Canine parvovirus first emerged in domestic dogs ( Canis familiaris ), most likely as a variant of the feline panleucopaenia virus. Relatively recently, canine parvovirus-2a and canine parvovirus-2b infections have been identified in both symptomatic and asymptomatic domestic cats, while canine parvovirus infections have also been demonstrated in wild felids. This report documents the first known case of canine parvovirus-2b detected in unvaccinated serval ( Leptailurus serva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…The clinical signs, gross lesions and histopathological findings in this case were similar to those in protoparvovirus infection described in other species (Oosthuizen et al, ; Stilwell, Anis, Wilkes, & Rissi, ; Xinyu et al, ). Although vesicular lesions are not commonly caused by protoparvoviruses, previous studies have demonstrated that protoparvovirus can infect keratinocytes and induce vesicular lesions on skin and tongue in pigs as well as skin and oral cavity in dogs (Favrot, Olivry, Dunston, Degorce‐Rubiales, & Guy, ; Woldemeskel, Liggett, Ilha, Saliki, & Johnson, ).…”
Section: Resultssupporting
confidence: 85%
“…The clinical signs, gross lesions and histopathological findings in this case were similar to those in protoparvovirus infection described in other species (Oosthuizen et al, ; Stilwell, Anis, Wilkes, & Rissi, ; Xinyu et al, ). Although vesicular lesions are not commonly caused by protoparvoviruses, previous studies have demonstrated that protoparvovirus can infect keratinocytes and induce vesicular lesions on skin and tongue in pigs as well as skin and oral cavity in dogs (Favrot, Olivry, Dunston, Degorce‐Rubiales, & Guy, ; Woldemeskel, Liggett, Ilha, Saliki, & Johnson, ).…”
Section: Resultssupporting
confidence: 85%
“…In addition, abnormalities were not detected in the heart. These characteristics of the infected tissues collected in this case were similar to those found in protoparvovirus infections in other species (Allison et al., 2013, 2014; Bucafusco et al., 2019; Oosthuizen et al., 2019; Viscardi et al., 2019; Wang et al, 2020).…”
Section: Resultssupporting
confidence: 83%
“…FPV or FPV‐like infections in wild felids have been reported in Puma concolor (Allison et al., 2014), Panthera tigris (Duarte et al., 2009; Wang et al., 2019) Panthera leo, Acinonyx jubatus, Felis lybicia (Calatayud et al., 2019; Steinel, Munson, van Vuuren, & Truyen, 2000), Genetta genetta (Calatayud et al., 2019) and Prionodon linsang (Inthong et al., 2019). Regarding CPV‐2 infections in wild felids, it have been reported in Felis bengalensis (Nakamura et al., 2001), Acinonyx jubatus , Panthera tigris (Steinel et al., 2000), Puma concolor , Lynx rufus (Allison et al., 2013, 2014) and Leptailurus serval (Oosthuizen et al., 2019). All of them showed high identity with circulating strains from domestic dogs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for infection by all investigated dog viruses was found. While CPV‐2 has been found in wild animals all around the planet (Allison et al., 2014; Canuti, Todd et al., 2020; Miranda & Thompson, 2016; Oosthuizen et al., 2019; Steinel et al., 2000; Wang, Tu et al., 2020), and there are reports of CAdV‐1 in wild canids (Balboni et al., 2021; Brandell et al., 2021; Dowgier et al., 2018; Millán et al., 2016; Pizzurro et al., 2017; Walker et al., 2016) and of CBuV‐1 in wolves (Melegari et al., 2019), to the best of our knowledge, this is the first report of MVC, CBoV‐2 and CachaV‐1 in wildlife. Furthermore, our data indicate that CBuV and CachaV‐1 were already circulating among wild animals (i.e., wolves) at least 11 and 10 years before their discoveries, respectively.…”
Section: Discussionmentioning
confidence: 99%